Design and Implementation of an Integrated Internal Collaboration and Communication Platform Using the SDLC Waterfall Method - Riyan Permana; Muhammad Riski Supandy; Raihan Nusantara; Wasis Haryono (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2026)
Collaboration and communication platforms play a critical role in supporting modern organizations, particularly those operating in hybrid and remote working environments. These platforms enhance workflow efficiency, improve coordination across teams, and facilitate seamless information exchange. This study aims to design and implement an integrated internal collaboration and communication system that unifies chat, discussion forums, file sharing, and internal video conferencing within a single platform. The system was developed using the Software Development Life Cycle (SDLC) with the Waterfall model, which includes requirement analysis, system design, implementation, and testing phases. Data collection was conducted through direct observation and structured interviews to identify user needs and determine system requirements. Functional testing was carried out to assess system performance, interface responsiveness, and feature reliability. The results indicate that all major functionalities work effectively, including real-time messaging, collaborative document editing, centralized file management, and virtual meeting capabilities. Overall, the proposed platform enhances coordination efficiency, reduces data fragmentation, and minimizes reliance on external third-party applications. This research provides a comprehensive and structured blueprint for developing integrated internal collaboration systems that support effective communication and centralized information management within organizational environments.